1998
DOI: 10.1002/(sici)1521-3765(19980416)4:4<707::aid-chem707>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Topology and Binding Area in Complexes of the Elongation Factor Proteins EF-Ts and EF-Tu⋅GDP fromThermus thermophilus: A Study by Protein Chemical Modification and Mass Spectrometry

Abstract: Amino acetylation of lysine residues in combination with mass-spectrometric peptide mapping of tryptic peptides has been applied to the characterization of surface topology and binding areas in complexes of the translation ± elongation factors EF-Tu and EF-Ts from Thermus thermophilus. Electrospray/ionization mass spectrometry (ESI-MS) yielded pH-dependent differences in the charge structure for the molecular ions of EF-Ts indicating differences in solution structure. The noncovalent EF-Tu´GDP complex was dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…The amino acid residues Thr-5 and Cys-6 have not been described in the X-ray structure [9]. The position of Arg- 16 …”
Section: Epitope Structure Identification Of a Monoclonal Antibody Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid residues Thr-5 and Cys-6 have not been described in the X-ray structure [9]. The position of Arg- 16 …”
Section: Epitope Structure Identification Of a Monoclonal Antibody Tomentioning
confidence: 99%
“…Affinity mass spectrometry approaches using proteolytic epitope excision and epitope extraction have been previously described in detail and applied in epitope identifications [14][15][16][17][18][19]. In the general analytical method [14][15][16][17]19], the immobilised ligand-binder (antigen-antibody) complex is subjected to limited proteolytic digestion, followed by mass spectrometric analysis of the eluted affinity-bound epitope peptide fragment (s). In the proteolytic step, the epitope is protected from digestion owing to the shielding of the ligand-binder interaction structure; hence, epitope excision on an immobilised immune complex is essential for isolation, specific dissociation and identification of the bound epitope.…”
Section: Introductionmentioning
confidence: 99%
“…Although NMR has higher resolution, MS had the clear advantage in terms of sensitivity, sample and time consumption, and the size limit of the proteins studied. At the same period, covalent labeling coupled to LC-MS started to emerge as a promising technique to probe protein surface topology [16][17][18][19][20]. A variety of chemical modifications (diethylpyrocarbonate, acetylation, carboxylation, oxidation) (reviewed in [21]) can be used to probe the surface accessibility of different amino acids.…”
Section: Hydrogen/deuterium Exchange and Covalent Labelingmentioning
confidence: 99%
“…When determining ligand-protein interaction surfaces by chemical modification footprinting, there is a direct competition between the ligand and the chemical probe to interact/react with the same amino group. As a result, the rate of modification has to be significantly lower than the ligand association rate (k on ) [19]. The dynamics of protein motions span a wide range of timescales, from pico-nanosecond thermal motions up to days for certain subunit exchanges between subunits.…”
Section: Ms-based Approaches Versus Classical Structural Biology Apprmentioning
confidence: 99%
“…28 Using simple modification chemistries such as acylation or succinylation, Glocker et al have shown that there is a clear correlation between the relative reactivity of specific amino acids and their surface (accessibility) topology in a protein. 29 Chemical cross-linking studies consist of treating proteins with cross-linkers prior to digestion. Cross-linkers covalently attach adjacent protein regions or protein subunits, therefore the resulting proteolytic fragments are good indications of the overall tertiary and/or quaternary protein structure.…”
Section: Protein Structure Elucidationmentioning
confidence: 99%